Occurrence of Phomopsis sp. causing cankers on pecan trees in Buenos Aires province, Argentina - Noelting, María Cristina (2016)
Production of pecan (Carya illinoiensis) continues to increase in Argentina, due mainly to its nutritional qualities and sustained export demand. In April 2014, the presence of cankers on branches and twigs was observed on pecan trees in the province of Buenos Aires, where the incidence ranged from 10 to 50% of the surveyed plantations (Fig. 1). Fungal isolates with morphological characteristics similar to those of Phomopsis (Sutton, 1980) were collected from cankers on potato dextrose agar after seven days of incubation in a growth chamber at 25°C with a 12 h photoperiod. Colonies in their early stages were whitish cottony (Fig. 2). They contained numerous, globose, brown to black pycnidia of 346.1 ± 59.8 μm × 286.4 ± 55.6 μm (Fig. 3), alpha hyaline conidia, fusiform to ellipsoid in shape, bigutulate with an average size of 6.8 ± 1.0 μm × 2.0 ± 0.2 μm, and beta filiform hyaline conidia, hamate in shape with average size of 21.6 ± 3.9 μm × 1.0 ± 0.1 μm.